Patriotism in the Political Discourse of the Union State of Belarus and Russia - O. V. Bakhlova; I. V. Bakhlov (Vestnik MGIMO-Universiteta)
The article delves into the nuanced challenge of crafting a cohesive unionwide patriotic agenda amidst escalating global tensions fueled, in part, by value conflicts. It scrutinizes the emergence of a patriotic discourse intricately woven into the institutional fabric of the Union State, the Russian Federation, and the Republic of Belarus, primarily steered by top political leadership at the domestic level. The overarching aim is to delineate the enduring themes and prevailing narratives within the political elites' patriotic discourse within the Union State, while exploring its potential conceptualization as a coordinating discourse to further integration objectives and as a countermeasure of "anti-soft power" against external value threats emanating from the collective West. Methodologically, the study draws upon discursive neo-institutionalism, employing qualitative content analysis of speeches delivered by the respective presidents of the two countries as its primary analytical approach.In the conclusions, the paper underscores the remarkable alignment between Russian and Belarusian stances on patriotic issues, particularly concerning their ideological underpinnings. Both underscore the imperative of safeguarding and preserving historical memory and traditional values as the cornerstone of their discourse. However, the analysis also sheds light on the conceptual complexities inherent in articulating sovereignty values by both participating countries. The practical implications underscore the necessity of further solidifying a shared socio-cultural space, harmonizing historical policies within both nations and within the Union State framework, and stimulating a "demand for integration" through the practical implementation of the principal directives outlined in the 2021 package of integration decisions.